2019
DOI: 10.1002/cctc.201802017
|View full text |Cite
|
Sign up to set email alerts
|

A Flower‐like Bismuth Oxide as an Efficient, Durable and Selective Electrocatalyst for Artificial N2 Fixation in Ambient Condition

Abstract: Ammonia is a basic industrial chemical, which is widely used in industry and agriculture. Traditional Haber–Bosch N2 fixation process is not environmentally friendly, which not only excessively consumes energy, but releases enormous amount of greenhouse gas. Electrochemical N2 reduction is an ideal alternative to N2 fixation, but it requires effective electrocatalyst for N2 reduction reaction (NRR). Herein, we develop a flower‐like β‐Bi2O3 catalyst for artificial N2 fixation with outstanding NRR performance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…As shown in Figure 2b and Figure S10d (Supporting Information), the in situ synthesized Bi NPs achieve a maximum NH 3 yield of 3.25 ± 0.08 µg cm −2 h −1 at −0.7 V versus RHE and maximum faradaic efficiency (FE) of 12.11 ± 0.84% at −0.6 V versus RHE, which are comparable with previously reported bismuth catalysts (Table S1, Supporting Information). [ 25–31,51–53 ] N 2 H 4 cannot be detected in the electrolytes after 1 h electrolysis by the Watt and Chrisp method (Figures S11 and S12, Supporting Information). The electrocatalytic stability of the Bi NPs was evaluated by consecutive cycling tests at −0.7 V versus RHE without changing the electrode and Nafion membrane.…”
Section: Figurementioning
confidence: 99%
“…As shown in Figure 2b and Figure S10d (Supporting Information), the in situ synthesized Bi NPs achieve a maximum NH 3 yield of 3.25 ± 0.08 µg cm −2 h −1 at −0.7 V versus RHE and maximum faradaic efficiency (FE) of 12.11 ± 0.84% at −0.6 V versus RHE, which are comparable with previously reported bismuth catalysts (Table S1, Supporting Information). [ 25–31,51–53 ] N 2 H 4 cannot be detected in the electrolytes after 1 h electrolysis by the Watt and Chrisp method (Figures S11 and S12, Supporting Information). The electrocatalytic stability of the Bi NPs was evaluated by consecutive cycling tests at −0.7 V versus RHE without changing the electrode and Nafion membrane.…”
Section: Figurementioning
confidence: 99%
“…17,18 Interesting nanostructures resembling natural shapes can be obtained. For instance, using solvothermal or hydrothermal strategies, ower-, [19][20][21][22][23] leaf-, 24,25 coral- [26][27][28][29][30] and seaurchin-like nanostructures have been reported recently, 31,32 demonstrating much enhanced performances in different applications. However, the biomimetic appearance of these patterns during the synthesis, in many cases, is not based on predictive mechanisms.…”
mentioning
confidence: 99%
“…Yang et al reported synthesis and NRR application of flower like structure β-Bi 2 O 3 . [249] Hydrothermal method was adopted to synthesize. It delivered NH 3 at 19.92 rate at −0.8 V in 0.1 m [250] As a result, it exhibited an efficiency as high as 10.26% at −0.5 V in 0.1 m HCl.…”
Section: Bi Compoundsmentioning
confidence: 99%